Unclosing Clinical Criteria and the Role of Cytokines in the Pathogenesis of Persistent Post-COVID-19 Headaches: A Pilot Case-Control Study from Egypt - Ahmed Abualhasan; Shereen Fathi; Hala Gabr; Abeer Mahmoud; Diana Khedr (Clinical and Translational Neuroscience)
(1) Background: Persistent post-COVID-19 headaches are emerging as a significant post-infection symptom. This study investigates the clinical characteristics of persistent post-COVID-19 headaches and the potential role of pro-inflammatory cytokines. (2) Methods: We conducted a pilot case–control study involving 84 participants divided into three groups: post-COVID with headache (n = 28), post-COVID without headache (n = 28), and healthy controls (n = 28). The detailed headache characteristics, including pain intensity, were assessed using the Visual Analog Scale (VAS). The serum levels of inflammatory cytokines (IL-6 and TNF-α) were measured. (3) Results: Post-COVID headaches predominantly presented as bilateral (53.6%) and throbbing (60.7%) in nature, with a median of 12 headache days per month and high pain intensity (median VAS score = 80). The associated symptoms were phonophobia (85.7%), fatigue (78.6%), and photophobia (75%). The serum levels of IL-6 and TNF-α were significantly higher in post-COVID headache patients than in the post-COVID without headache and healthy control groups (p < 0.001). A Receiver Operating Characteristic analysis showed that the circulating levels of IL-6 and TNF-α could discriminate our study groups at cutoffs with variable sensitivity and specificity. (4) Conclusions: Persistent post-COVID-19 headaches have diverse clinical characteristics and are associated with elevated circulating levels of pro-inflammatory cytokines, suggesting a potential underlying neuroinflammation.